Neuroglobin protects astroglial cells from hydrogen peroxide‐induced oxidative stress and apoptotic cell death. Issue 1 (27th December 2016) - Amri, Fatma; Ghouili, Ikram; Amri, Mohamed; Carrier, Alice; Masmoudi‐Kouki, Olfa
Abstract: Oxidative stress, resulting from accumulation of reactive oxygen species, plays a critical role in astroglial cell death occurring in diverse neuropathological conditions. Numerous studies indicate that neuroglobin (Ngb) promotes neuron survival, but nothing is known regarding the action of Ngb in astroglial cell survival. Thus, the purpose of this study was to investigate the potential glioprotective effect of Ngb on hydrogen peroxide (H2 O2 )‐induced oxidative stress and apoptosis in cultured mouse astrocytes. Incubation of cells with subnanomolar concentrations of Ngb (10 −14 –10 −10 M) was found to prevent both H2 O2 ‐evoked reduction in surviving cells number and accumulation of reactive oxygen species in a concentration‐dependent manner. Furthermore, Ngb treatment abolishes H2 O2 ‐induced increase in mitochondrial oxygen consumption rates. Concomitantly, Ngb treatment rescues H2 O2 ‐associated reduced expression of endogenous antioxidant enzymes (superoxide dismutases and catalase) and prevents the stimulation of the expression of pro‐inflammatory genes (inducible nitric oxide synthase, cyclooxygenase‐2, and interleukin (IL) IL‐6 and IL‐33). Moreover, Ngb blocks the stimulation of Bax (pro‐apoptotic) and the inhibition of Bcl‐2 (anti‐apoptotic) gene expression induced by H2 O2, which in turn abolishes caspase 3 activation. The protective effect of Ngb upon H2 O2 induced activation of caspase 3 activity and cell death can be accounted for by activation of protein kinase A and mitogen‐activated protein kinase transduction cascade. Finally, we demonstrate that Ngb increases Akt phosphorylation and prevents H2 O2 ‐provoked inhibition of ERK and Akt phosphorylation. Taken together, these data demonstrate for the first time that Ngb is a glioprotective agent that prevents H2 O2 ‐induced oxidative stress and apoptotic astroglial cell death. Protection of astrocytes from oxidative insult may thus contribute to the neuroprotective effect of Ngb. Abstract : We proposed the following cascade of the glioprotective action of neuroglobin (Ngb) against H2 O2 ‐induced astrocyte damage and apoptosis. Ngb, through activation of the PKA, MAPK/ERK and phosphatidylinositol 3′‐OH kinase/Akt signaling pathways, prevents accumulation of ROS, the inhibition of antioxidant enzymes (superoxide dismutase and catalase) and Bcl‐2 expression and the increase of pro‐inflammatory genes (inducible nitric oxide synthase, cyclooxygenase‐2, IL‐6 and IL‐33) mRNA levels which preserve mitochondria activity and abolish caspase‐3 activation induced by H2 O2 in cultured mice astrocytes. These data suggest that astroglia‐secreted Ngb may confer neuroprotection in neurodegenerative diseases and may allow the development of new strategies for cerebral injury treatment.